2003
DOI: 10.1002/art.10939
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignant lymphomas in patients with rheumatoid arthritis and in their first‐degree relatives

Abstract: Objective. Patients with rheumatoid arthritis (RA) are at increased risk for malignant lymphomas. Both conditions display a familial aggregation, and there are reports of RA and malignant lymphomas occurring in the same families. This study was undertaken to determine the risk of malignant lymphomas in first-degree relatives of RA patients, in order to investigate whether the increased risk of malignant lymphomas in RA could be due to genetic or environmental risk factors common to both conditions, rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
4
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(183 citation statements)
references
References 36 publications
10
155
4
14
Order By: Relevance
“…Another limitation would be that not all affected family members are hospitalized, in which case the numbers of hospitalizations would be decreased and would probably preferentially include only those patients with severe disease at presentation. In the case of RA, it has been estimated that up to 75% of Swedish patients have been hospitalized for RA at one time or another (29,30). A crude prevalence of hospitalization can be estimated by dividing the number of RA patients (47,361) by 8.5 million (the Swedish population over the study period minus the number of persons lacking family links), yielding a crude prevalence of hospitalization for RA of 0.56%; this is 80% of the assumed true population prevalence of RA (0.7%) in Sweden (31).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation would be that not all affected family members are hospitalized, in which case the numbers of hospitalizations would be decreased and would probably preferentially include only those patients with severe disease at presentation. In the case of RA, it has been estimated that up to 75% of Swedish patients have been hospitalized for RA at one time or another (29,30). A crude prevalence of hospitalization can be estimated by dividing the number of RA patients (47,361) by 8.5 million (the Swedish population over the study period minus the number of persons lacking family links), yielding a crude prevalence of hospitalization for RA of 0.56%; this is 80% of the assumed true population prevalence of RA (0.7%) in Sweden (31).…”
Section: Discussionmentioning
confidence: 99%
“…497 Similarly, Gridley et al 498 reported a significant positive association with RA among Swedish patients (SIR 5 1.88, 95% CI: 1.3-2.6). In a similar study with longer follow-up (for a maximum of 35 years), Ekstr€ om et al 499 estimated that RA patients had nearly twice the risk of NHL (SIR 5 1.89, 95% CI: 1.72-2.07), and additionally found that first-degree relatives of RA patients were not at significantly increased risk of NHL. The latter finding suggests that the excess risk of NHL in RA patients may be a result of the disease or its treatment, rather than shared genetic susceptibility.…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 94%
“…Recently, MTX has been used as an anchor drug for the treatment of RA (1). However, RA patients have a high risk of onset of lymphoproliferative disease (LPD) (2). Furthermore, LPD developed by immunodeficient patients treated with MTX is defined as MTXassociated LPD (MTX-LPD) in the 2008 World Health Organization Classification of Tumours of Haematopoietic and Lymphoid Tissues (3).…”
Section: Introductionmentioning
confidence: 99%